Kenya (national scale), in-season crop modeling for monitoring food security shocks - CGIAR Platform for Big Data in Agriculture (2020)
Proof of concept: the partners demonstrated a capability to detect crop onset in-season using remote sensing and validated this with on-the-ground partners.